ANALISIS MOTIVASI BELAJAR SISWA DALAM IMPLEMENTASI PENDEKATAN PEMBELAJARAN MENDALAM (PM) MATERI SISTEM PENCERNAAN DI SDN 2 GOLONG - Armi Larasati; Daroe Iswatininigsih; Zulkifli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze students' learning motivation in the application of the Deep Learning Approach to digestive system material at SDN 2 Golong. The research problem focuses on the need for a learning approach that not only strengthens conceptual understanding but also fosters students' intrinsic motivation. The research method uses a qualitative approach with a case study design, with data obtained thru observation, interviews, and documentation of school principals, teachers, and 20 fifth-grade students. The research results show that implementing PM thru the stages of preparation, exploration, application, and reflection is able to create meaningful, conscious, and enjoyable learning experiences. The PM approach has a positive influence on students' learning motivation by increasing active engagement and deeper conceptual understanding. However, challenges were found in the imbalance of participation in group work. More structured teacher intervention, including role distribution, is needed to ensure equal participation. The limitations of this study include the small number of subjects and its qualitative nature, so further research with a larger population and mixed methods is recommended to test the effectiveness of this approach more comprehensively.